Experiences of inclusive youth participation with a focus on Global Citizenship (Journal of Parents and Teachers, 2023)
In the common horizon of achieving fairer and more inclusive societies, attention to diversity is a current challenge, but also an opportunity to do so. This article presents experiences of accompanying processes of inclusive youth participation, in which young people with functional diversity have joined educational proposals from the approach of Global Citizenship to act as agents of change being a citizenship committed to society.
Keywords: attention to diversity; functional diversity; global citizenship; social transformation; inclusion; education